Identification and Quantification of Corn, Soybean and Cotton Genetically Modified by Real Time PCR - Sawazaki, Haiko E.; Duarte, Aildson P.; Fuzatto, Milton G.; Sawazaki, Eduardo; Henrique, Silvio; de Ponte, Jessica F.; Nogueira, Larissa (Scientific Research Publishing, 2015)
In order to obtain a cheaper method for quantification of transgenic events in corn, soybeans and cotton, primers for real time PCR have been developed and optimized, with fluorescent BRYT Green system. The DNA was extracted from grains, with and without event, by CTAB method. The following events have been studied for corn: MON810, Bt11, MON89034, GA21, TC1507, NK603, MIR162, PRO3; Soybean: GTS-40-3-2, MON87701; MON89788; for cotton: MON1445, MON531, LLCotton25, 281-24-236; 3006-210-23, GHB614, T304-40; GHB119, MON15985, MON88913, besides the respective primers for the endogenous genes of corn, soybean and cotton. The sensitivity was 0.057%, the coefficient of linearity R2 ranged from 0.98 to 0.99 and the efficiency of PCR 0.9 to 1.1. The quantification of events ranged from 92 to 115, with a relative error (RE) from 2 to 18%, and a variance of 0.33 to 3.0. The precision acceptance criterion was observed for all analyses, as well the repeatability and reproducibility. As it was found that the measurement of accuracy and reproducibility were within the international acceptance criterion, it may infer the robustness of the methodology. Therefore, the results from replicates with two different technicians, and validation of results by comparison with those obtained by Eurofins Brazil, showed the possibility of specific and quantitative analysis of transgenic events with a cheaper method with sensitivity, repeatability and robustness.
Keywords: Transgenic Events; Quantification; Corn; Soybean; Cotton